Pemberdayaan Taman Pendidikan Alqur’an (TPA) Dalam Meningkatkan Motivasi Belajar Alqur’an di Desa Koto Teluk - Wisda, Rini Syevyilni (Jurnal Pengabdian kepada Masyarakat Radisi, 2025)
The low interest of the generation to study the science of Islamic education, reading and writing the Qur'an is caused by environmental influences, technological developments so that many children choose to play rather than study in the Qur'an park, this is also influenced by the lack of management of the Qur'an parks. The method used in this community service activity through the ABCD technique with this method used to focus on the strength of the potential assets owned by the community at the service location related to existing resources. The abstract is not in the form of mathematics, questions, and guesses. The abstract is also not a direct copy of the existing sentence, with this method it is expected to be able to develop existing resources. Empowerment of the Qur'an Education Park is carried out in increasing interest in reading the Qur'an by using a fun learning strategy pattern with an individual and group learning system and using a fun learning model, in the learning process not only reading, reciting the Koran but there is a memorization process and others.